KARYUU ROUJIN SEBAGAI GOLONGAN LANSIA MISKIN DI JEPANG - Elsy, Putri (Japanology: The Journal of Japanese Studies, 2023)
The changes in the Japanese population with an increasing number of elderly and the decline in the number of children caused a problem in society. Currently many Japanese elderlies live in poverty. These elderly are known as karyuu roujin. The term karyuu roujin was introduced by Takanori Fujita, a social worker in 2015. This term became the starting point for the depiction of poverty from the actual situation of the elderly in Japan. The term karyuu roujin is defined as old people who live with basic welfare standards and worried about their living conditions. Now, Japan's first baby boomer generation getting old and poverty have become commonly seen among these elderly people. It is estimated that there are around 6-7 million karyuu roujin. The purpose of this paper is to describe karyuu roujin as a class of poor elderly in japan and the problems faced in old age. The method used is qualitative with descriptive analysis. The results indicate that with longer life spans, the elderly are becoming an increasingly large class of the poor in the Japanese population. The problems faced by these poor elderly people include a small pension, high medical costs, no children or family to ask for help. The impact of this poverty is that many elderly people commit criminal acts and suicide.